Sustainable development goals and Millennium Development Goals: an analysis of the shaping and negotiation process - Yiu, Lichia; Saner, Raymond (2014)
This article analyses the emerging scope of the Sustainable Development Goals (SDGs) as the successor development instrument to the Millennium Development Goals (MDGs) which are scheduled to end on 31 December 2015. The top priorities of the stakeholders involved in the shaping and negotiation process include poverty eradication, water sanitation, energy, economic growth, green growth, governance and employment. Current trends appear to favour a progression of the shaping and negotiation process which goes beyond the established MDG goals. - Reproduced.
Keywords: Millennium Development Goal